EVOLUSI DOKTRIN ULTRA VIRES DALAM TATA KELOLA KEPUTUSAN DIGITAL DAN BIG DATA PADA PERUSAHAAN MODERN - Iman Sjamsu Rahardjo (Jurnal Kewirausahaan Bukit Pengharapan, 2025)
The rapid transformation of the digital economy has significantly reshaped corporate decision-making, particularly in high-risk investments involving advanced technologies and big data. In this context, the doctrine of ultra vires traditionally understood as actions taken beyond a company’s stated objectives requires reinterpretation to remain relevant. This study aims to examine the evolution of the ultra vires doctrine in Indonesian corporate law and to reassess its relevance within digital governance and data-driven decision-making. This research employs a normative juridical approach combining statutory and conceptual analysis, primarily referring to Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 27 of 2022 concerning Personal Data Protection. The findings indicate that ultra vires has evolved from a rigid doctrine of invalidity into an evaluative mechanism defining the outer limits of directors’ authority. The relationship between ultra vires and the business judgment rule is not contradictory but complementary: ultra vires operates as an external boundary, while the business judgment rule provides conditional protection for rational business risks. This article argues for a functional-adaptive reinterpretation of ultra vires by integrating it with fiduciary duties and digital risk governance standards. Such an approach helps balance innovation flexibility with legal certainty, ensuring that corporate law remains responsive to the dynamics of the data-driven economy without compromising accountability.